THE WORLD THROUGH THE CHILD’S EYES-THE JOURNEY TOWARDS ELIMINATION OF CHILDHOOD BLINDNESS IN GHANA - THE KORLE-BU EXPERIENCE. - Essuman, V.A. (My University, 2013)
The World Health Organization (WHO) has identified the prevention, treatment and control of blindness and visual impairment in childhood as a priority area of work worldwide. This is targeted under the Vision 2020 Initiative for Elimination of Avoidable Blindness. The initiative requires specialised paediatric ophthalmology teams and units to achieve this goal, but these are non-existent in most developing and under-developed countries. WHO with its Partners and some Governments embarked on the establishment of such units in some deprived countries on pilot basis, and Ghana was one of the beneficiary countries. The Child Friendly Eye Care Centre (CFECC) was set up in Korle-Bu Teaching Hospital in Accra under the Phase I of the WHO/Lions Club International/ Goverment of Ghana Project for the Elimination of Childhood Blindness in Ghana. The experiences from the CFECC is presented here, looking at the achievements and the strengths, weaknesses, opportunities and threats (SWOT) analysis of the project.